Helping or Enforcing? Service, Security, and Occupational Identity in Female Criminal Justice Students’ Intent to Enter Law Enforcement - Basham, Sherah L.; French, Ashley T.; Bray, Bethany; Mitsch, Jennifer; Slaughter, Anovia (International Journal of Criminology and Sociology, 2026)
Women remain significantly underrepresented in law enforcement, comprising less than 14% of sworn officers in the United States despite decades of recruitment initiatives. Understanding what motivates or deters female criminal justice students from pursuing law enforcement careers is fundamental for addressing this persistent gap. This study examines the factors influencing female criminal justice students' intent to pursue a law enforcement career, using survey data collected from 292 female students enrolled in criminal justice programs across the United States in 2020. Using exploratory factor analysis, three motivational scales were constructed: pay and security, service orientation, and occupational identity. Binary logistic regression results indicate that occupational identity, characterized by tangible policing symbols such as carrying a weapon and wearing a uniform, was the strongest positive predictor of intent to pursue a career in law enforcement. Conversely, both service-oriented and pay-and-security motivations were associated with lower odds of pursuing a career in law enforcement. Except for a marginal association for the smallest racial subgroup, demographic factors (age, marital status, child status, and political affiliation) were not significant predictors. Findings are discussed in relation to the gendered construction of law enforcement identity, the service motivation paradox, and their implications for recruitment policy.